Implementação de projeto de outorga para o gerenciamento ambiental da água de abastecimento da cidade universitária José da Silveira Netto - REIS, Alzira Maria Ribeiro dos (Universidade Federal do Pará, 2020)
The present study was developed in the University City Prof. José da Silveira Netto, headquarters of the Federal University of Pará (UFPA), in the city of Belém, in order to evaluate the current status of regularity regarding the Granting of Right to Use Water Resources to the managing body, Environment and Sustainability Secretariat ( SEMAS / PA). Granting is one of the instruments of the National and State Policy of Water Resources and aims to ensure the quantitative and qualitative control of water uses and the effective exercise of rights to access the water. The objective is to propose the necessary procedures for the implementation of a granting project for the environmental management of the water supply of the university city José da Silveira Netto, being discussed in the body of the dissertation on Water Resources Management and its legal aspects, National and State Water Resources Policy, and if they have already been implemented in the state of Pará, with emphasis on the granting of the right to use water resources, legal aspects, infractions and penalties. The methodology was carried out through qualitative, quantitative and field research, based on a documentary and bibliographic source, Technical Execution Report of FEMAC that were available by the UFPA prefecture, data from the Mineral Resources Research Company (CPRM), direct conversations in SEMAS, as well as data collection for administrative and technical procedures, available on the agency's own website. According to the data collected on the current conditions of the well, it was found that it is not fully adequate to grant the application for granting water use, since it is not corresponding the standards requirements towards the environmental agency, in view of problems with technical orders and sanitation, as well as the buffering of inoperative wells with the objective of restoring the original conditions of the aquifer and avoid contamination through the well. In view of the above, and in order to supply these requirements, it was suggested to the institution's maximum administrator a model of granting the right to use water resources to the José da Silveira Netto University City, and the appointment of a multidisciplinary team, with the presence of a professional in the field of geology, solving the irregularities due to being a risk to the safety of the well and to the university community, in order to comply with current legislation, as well as all the technical restrictions proposed by the responsible environmental agency.